Public attitudes to genetic technology for invasive pest control and preferences for engagement and information: a segmentation analysis - Hobman, Elizabeth V.; Mankad, Aditi; Carter, Lucy; Collins, Kerry (Frontiers in Bioengineering and Biotechnology, 2025)
Advances in genetic technology hold promise in managing the increasing problem of invasive pests. The current study sought to improve our understanding of public perceptions, and potential public engagement pathways and information needs as the technology is researched and potentially developed for deployment. A survey of 1,149 Australians was conducted, and the sample was segmented into 4 groups based on their attitudes: Certain Objectors, Fence Sitters, Cautious Supporters, and Certain Supporters. ‘Light touch’ engagement activities appeared to satisfy most people; yet more intensive engagements could be appropriate for a small group who hold negative views towards the technology. Across the board, people wanted to know about the potential risks, and the regulation and controls surrounding the gene editing technology. Those who held more positive views also showed an interest in the scientific processes and techniques, while people who held more negative views wanted to know what was being done to deal with social and ethical issues. The results provide insight into 1) the diversity of views, and associated beliefs and feelings, among the public when confronted with a synthetic biology solution to an environmental problem, 2) how public engagement activities can be tailored to align with people’s engagement beliefs and stated preferences, and 3) what issues biotechnology developers should address as they endeavour to design genetic technology in a socially responsible way.